2002
DOI: 10.1081/css-120015913
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Litterfall and Decomposition in a Forest of the Chaco Argentino

Abstract: Within an equilibrated forestry ecosystem there is a close relationship between annual leaf litterfall to the soil and litter decay constant. The goal of this work was to determine the leaf litterfall of the black Carob tree [Prosopis nigra (Griseb) Hieron.] and Quebracho Colorado Chaqueño (Schinopsis balansae Engl.) and the decay constants for leaf litter in the Parque Chaqueño Húmedo Argentino. The annual decay constant (k ) was calculated using a single exponential model. The Quebracho Colorado Chaqueño pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Therefore, the leaves of P. affinis, C. ehrenbergiana, and P. nigra may lose greater labile substances through leaching (watersoluble substances) than in A. caven; Aceñolaza & Gallardo (1994) and Prause et al (2002Prause et al ( , 2012 confirmed the occurrence of rapid labile and water-soluble substances leaching in species of subtropical forests used for silvopastoral activities.…”
Section: Secondary Forestmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, the leaves of P. affinis, C. ehrenbergiana, and P. nigra may lose greater labile substances through leaching (watersoluble substances) than in A. caven; Aceñolaza & Gallardo (1994) and Prause et al (2002Prause et al ( , 2012 confirmed the occurrence of rapid labile and water-soluble substances leaching in species of subtropical forests used for silvopastoral activities.…”
Section: Secondary Forestmentioning
confidence: 90%
“…Prause et al (2002) observed that in Argentine Chaco forests, Schinopsis balansae Engl. was the species that most largely contributed litterfall to the soil (although it had a lower decomposition constant), compared with litterfall inputs of P. nigra; therefore, this system seems to be have differently from the Mesopotamian Espinal.…”
Section: Temporal Patterns Of Leaf Weight Lossmentioning
confidence: 99%
“…Approximately 90% of the net primary production of terrestrial ecosystems is recycled through the decomposition of litterplant residues that fall to the soil, including leaves, branches, and reproductive structures of plants (Graça et al, 2007). The continued return of organic matter and nutrients to the soil through litter decomposition is a central process in the biogeochemical cycles of forest ecosystems and the maintenance of soil fertility and soil invertebrates and microorganisms (Prause et al, 2002;Lu and Liu, 2012;Aryal et al, 2015). Decomposition is influenced by regional factors such as precipitation and temperature (Epstein et al, 2002;Zhang et al, 2008;Schilling et al, 2015) and local factors like soil moisture (Lennon et al, 2012;Evans and Wallenstein, 2014), the chemical composition of leaves (Talbot and Treseder, 2012;Jackson et al, 2013;Zanne et al, 2015), forest successional age (Xuluc et al, 2003;Ostertag et al, 2008;Schilling et al, 2015), topography (Sariyildiz et al, 2008;von Arx et al, 2012), and composition and activity of decomposers (Schilling et al, 2015;Strickland et al, 2015;Da Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%